(untitled) - Perez-Corral, Violeta Q. (Quezon city, Philippines, 2001)
The guidebook is published in response to the needs of our partners. In particular, the issues on privatization have been 'hot issues' among the NGOs in many Asian countries. The ADB approved the Poverty Reduction Strategy (PRS) in the fall of 1999, and poverty reduction has been identified as its "overarching goal".
Keywords: Các tổ chức chính phủ,Government business enterprises; Châu Á,Asia